Assessment of the security risk to people and property from ordnance explosion effects in the Serbian armed forces - Stojanović, Dejan S. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The research goal is to enable prediction of events in the incoming period on the basis of a large number of collected relevant data that may represent a potential risk and the danger of ordnance explosion effects in the Army of Serbia. The realization of the objectives of the research requires the use of appropriate methods and techniques for dating and study of existing teoretical and practical solutions as well as proposing new ones in the areas of interest. During the research, the following scientific methods were used: comparative method, content analysis and positivist method. The investigation has covered situations which may arise at workplace due to various threats caused by both the human factor and chains of events, followed by the identification of potential forms of risk to people and property by ordnance explosion effects in the Army of Serbia. The collected data on potential forms of endangering people and property by ordnance explosion effects were analysed and their positive and negative consequences were discussed. The levels of safety risks to people and property from ordnance explosion effects are assessed and decisions are made about the forms of threat and to what extent they will be dealt with in the future. Assessment of the safety risk to people and property from the effects of ordnance explosions The assessment of the safety risk to people and property from the effects of ordnance explosions comprises a theoretical treatment of certain procedures or stages which are successively connected, interdependent and which concern the whole Army of Serbia. On the basis of their analysis, decisions will later be made to ease or eliminate hazards, risks and threats from the effects of ordnance explosions in the Army of Serbia. This involves the following procedures or phases for treating such hazards, risks and threats: - defining the problem of the effects of ordnance explosions; - identifying potential hazards, risks and threats; - analysing potential hazards, risks and threats; - evaluating the levels of potential hazards, risks and threats. Defining the problem of ordnance explosion effects Defining the problem arising from the effects of ordnance explosionsrepresents an overview of all the problems that may arise in the Serbian Army due to possible occurrence of ordnance explosion effects. Problems that affect the probability of occurrence of hazards, risks and threats of the effects of explosions of ordnance in the Serbian Army are defined on the basis of factors that can cause them: - human factor with the intention to cause an event with harmful consequences caused by foreseeable or unforeseeable events. - certain events or occurrences due to accidents or force majeure which pose a risk to the safety of members of the Army of Serbia. Identifying potential hazards, risks and threats Identifying potential hazards, risks and threats was done on the basis of all relevant and updated information gained from the study, namely: - space hazards, risks and threats, including: area security, area safety, space conditionality and other space hazards, risks and threats, - human hazards, risks and threats, including: education, respect the rules and regulations, injuries and other human hazards, risks and threats, - explosive hazards, risks and threats, including: obsolete ordnance, prohibited ordnance, damaged ordnance and other explosive hazards, risks and threats, - tehnical - technological hazards, risks and threats, including: detecting ordnance, ordnance production , ordnance smuggling and other tehnical - technological hazards, risks and threats. Analysis of potential hazards, risks and threats Potential hazards, risks and threats of ordnance explosion effects are analysed based on reviewed data collected from previously identified hazards, risks and threats as well as their negative and positive effects. Consequences can be determined based on the outcome of an event or series of events, ie, on the basis of available information, known data and events. Negative consequences occur in cases where the outcome of each event involving ordnance as the main cause is most frequently disastrous, and positive effects occur in cases in which disaster is avoided and the safety of people and property is not threatened to a greater extent. Assessment of the level of potential hazards, risks and threats Assessing the level of potential hazards, risks and threats of ordnance explosion effects is a prerequisite for determining which hazards, risks and threats should be considered and to which extent, depending on the calculated levels of potential hazards, risks and threats of the effects of ordnance explosions. The level of hazards, risks and threats of the effects of ordnance explosions can be calculated using the following pattern N = V × P. According to the results based on the product of probability and consequences (N = V × P), a high level of hazards, risks and threats of the effects of ordnance explosions is not negligible for the Army of Serbia, and should be seriously addressed. Conclusion Ordnance explosions in ordnance production facilities, ordnance warehouses, barracks and military training grounds point to the necessity to apply all available resources to minimize such events which result in losses of human lives and property. Since they have occurred in the previous period, there is high likelihood that they may occur again, which implies that prevention measures must be taken to reduce or eliminate them completely.. Each member of the Army of Serbia should be provided with continuously safe working environment; in addition, it is necessary to provide healthy environment for all citizens of the Republic of Serbia. In order to reduce hazards, risks and threats of ordnance explosion effects to a lower level and thus increase the safety and security of people and property in such occurrence, in the Army Serbia, it is necessary to design a strategy to eliminate or mitigate the safety and security risks to people and property from ordnance explosion effects in the Army of Serbia.